IMPACT OF FOOD LABELING ON CONSUMERS BUYING DECISION (GEORGIAN CASE) (International Journal of Innovative Technologies in Economy, 2018)
Labeling is a universal phenomenon for the characterization of food products. The paper studies the role of food labeling in consumer behavior in Georgian Market. The main focus is on the awareness of consumers about food labeling, which is presented, as the most important issue of social marketing. The current study evaluates the impact of food labeling on consumer buying decision. To determine the attitude of Georgian consumers to food labeling, we conducted a marketing research. The study revealed the strong relationship between interest and awareness about food labeling, as well as among awareness, reliability and satisfaction about food labeling and consumer buying decision.